Representasi Gender dalam Ketoprak Gaul 2024: Analisis Wacana Kritis Sara Mills - Pratiwi, Sepdiyanti Rizki; Supriadi, Didik; Astuti, Eka Yuli (Lingua Susastra, 2025)
Ketoprak Gaul 2024 represents the revitalization of Javanese performing arts that combines traditional culture and modern communication styles. This study aims to reveal gender representations and power relations in four Ketoprak Gaul 2024 scripts, namely Ulupati, Sabdha Malaya, Layung Girah, and Luh Tresna, using Sara Mills' critical discourse analysis. A literature review shows that previous studies have focused on literary texts and media, without touching on modern folk performance texts. This study uses qualitative methods with analysis of dialogue, narrative, and stage directions, supplemented by interviews with lay readers and experts as triangulation sources. The focus of the analysis is on the position of the subject, object, and reader to explore the construction of ideology and power in the text. The results show that men are constructed as the dominant subject, while women become subordinate objects with limited space for resistance. However, there is also the potential for social criticism of feudalism and patriarchy through reflective dialogue. This study concludes that Ketoprak Gaul 2024 still reproduces patriarchal discourse structures, but at the same time presents the potential for social criticism of the traditional Javanese gender order, thereby enriching the study of gender representation in modern folk performances.